2019
DOI: 10.31386/dmj.2019.12.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Status of Serum Magnesium in Children With Type 1 Diabetes Mellitus: Relation to Glycemic Control

Abstract: Background: Magnesium has an important role in the metabolism of carbohydrate so that it may affect the release and activation of insulin which is the hormone that controls levels of blood glucose. Different studies all over the world have found a low serum Magnesium in diabetic children with poor glycemic control reflected mainly by glycated hemoglobin (HbA1c) level. Our aim was to evaluate the serum magnesium status in children with type 1 diabetes and to assess its relation to glycemic control. Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…In the liver, a reduced Mg2 + -dependent pyruvate dehydrogenase activity and TDP can shift the glucose metabolism into the oxidative phase of the pentose phosphate pathway and this leads to an increased NADPH production. [32]. NADPH is an important redox cofactor for metabolic processes, including fatty acid biosynthesis, and therefore increased synthesis of triglycerides and low density lipoproteins, and hence greater accumulation of triglycerides in adipocytes which increases the extent of obesity and the risk of obesity Morbidity such as dyslipidemia, metabolic syndrome and type 2 diabetes [33,34] and in a study that indicated that the high concentration of triglycerides is linked to insulin resistance through the entry of free fatty acids into the liver and thus increase the storage of fat in adipose tissue, which leads to obesity [35,36] On the other hand, recent studies have linked magnesium with kidney patients [37] and polycystic ovary syndrome [38] and hypothyroidism patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, a reduced Mg2 + -dependent pyruvate dehydrogenase activity and TDP can shift the glucose metabolism into the oxidative phase of the pentose phosphate pathway and this leads to an increased NADPH production. [32]. NADPH is an important redox cofactor for metabolic processes, including fatty acid biosynthesis, and therefore increased synthesis of triglycerides and low density lipoproteins, and hence greater accumulation of triglycerides in adipocytes which increases the extent of obesity and the risk of obesity Morbidity such as dyslipidemia, metabolic syndrome and type 2 diabetes [33,34] and in a study that indicated that the high concentration of triglycerides is linked to insulin resistance through the entry of free fatty acids into the liver and thus increase the storage of fat in adipose tissue, which leads to obesity [35,36] On the other hand, recent studies have linked magnesium with kidney patients [37] and polycystic ovary syndrome [38] and hypothyroidism patients [39].…”
Section: Discussionmentioning
confidence: 99%